Student’s Creative Thinking Skill and Belief in Mathematics in Setting Challenge Based Learning Viewed by Adversity Quotient - Satrio Ardiansyah, Adi; Junaedi, Iwan; Asikin, Mohammad (Universitas Negeri Semarang, 2018)
Creativity, belief in math, and adversity quotient play a significant role in mathematics. This study aims (1) to know the quality of mathematics learning settings Challenge Based Learning on student’s creative thinking skill and belief in math; (2) to examine the influence of belief in math to creative thinking skill; (3) to describe student’s creative thinking skill in settings Challenge Based Learning viewed by Adversity Quotient; and (4) to describe student’s belief in math in settings Challenge Based Learning viewed by Adversity Quotient. The design of this study was mixed methods of concurent embedded type. The study subjects were students of SMP Negeri 1 Semarang grade VIII who selected by Adversity Quotient. The result showed that (1) mathematics learning setting Challenge Based Learning is qualified to student’s creative thinking skill and belief in math; (2) there was the influence of belief in math to student’s creative thinking skill amount 12,8%; (3) camper’s students were only able to satisfy flexibility and climber’s students were able to satisfy fluency, flexibility, and novelty; and (4) there was a camper’s students was able to satisfy belief about self and climber’s students were able to satisfy belief about mathematics education, belief about the self, and belief about the social context.